Characterization of the novel HLA‐C*07:724 allele by sequencing‐based typing. (29th April 2019) - Elsermans, Vincent; Visentin, Jonathan; Top, Isabelle; Varlet, Pauline; Labalette, Myriam
Abstract : HLA‐C*07:724 differs from HLA‐C*07:02:01:01 by one nucleotide substitution in codon 9 in exon 2.